Sinergi UMKM Dan Wisata Dalam Revitalisasi Desa Wisata Kebangsaan, Kabupaten Situbondo - Mijiarto, Joko; Gusriza, Fondina; Andrea, Garsione Agni; Sirait, Lidya Listrayani (Jurnal Ilmiah Pariwisata, 2023)
Wonorejo Village is one of the pioneers in developing tourism villages in Situbondo Regency. To support the development of the tourism village, the manager of the tourism village must continue to innovate in developing attractiveness. One that can be developed into an attraction is the creative industry and community entreprise. The research aims to identify and develop a creative industry-based tourism program in Wonorejo village. The research was conducted in July 2022 in Wonorejo Village, Situbondo Regency, East Java. The research was carried out by observation and in-depth interviews with creative industry and community enterprise players in Wonorejo Village. Based on the results of the study, Wonorejo Village has several creative industries that can be developed including spice coffee, milk processing, ecoprint batik, nata decoco, pindang and tuna shreds, shrimp paste / petis, honey, and sour fruit syrup. Currently, these businesses have not been integrated into tourism activities and some are no longer in production due to the absence of orders and the lack of tourists to the National Tourism Village. Keywords: Creative Industry, Community Enterprise, Rural Tourism, Wonorejo Village